Comparison of total intravenous ketamine and propofol anaesthesia in acepromazine- dexmedetomidine sedated cats (2019)
Total intravenous anaesthesia (TIVA) refers to the induction and maintenance of general anaesthesia with drugs administered solely by the intravenous (IV) route. Presently, ketamine and propofol are popular and in use for TIVA in small animals. This study compared ketamine and propofol anaesthesia in cats premedicated with acepromazine-dexmedetomidine combination. Six indigenous Nigerian local cats were premedicated with intramuscular injection of acepromazine (0.2mg/kg) and dexmedetomidine (40μg/kg) mixture, followed by induction of anesthesia with either bolus propofol (1mg/kg) or ketamine (0.5mg/kg) IV 20 min later. Maintenance of anesthesia for 2h was achieved with continous fl uid administration using dose of 0.5ml/8ml and 0.05ml/8ml in lactated Ringers solution for propofol and ketamine respectively. One week space was allowed between protocols in the crossover experiment. Anesthetic indices, cardiopulmonary parameters, and rectal temperature were recorded at 5 min intervals for 2 h. Duration of anti-nociception with ketamine protocol was not signifi cantly (p<.05) different from the corresponding propofol protocol value while recovery time and standing time were signifi cantly (p<.05) different between either protocol. Systolic arterial pressure, Diastolic arterial pressure and mean arterial pressure were significantly (p<0.05) lower for propofol protocol than ketamine protocol, while SpO2 responses were significantly (p<0.05) higher for propofol protocol than ketamine protocol. There was no statistically significant difference between other physiological variable means recorded for both protocols. It was concluded that ketamine and propofol protocols produced satisfactory anaesthetic induction and maintenance in healthy cats premedicated with acepromazine-dexmedetomidine. Used in the same manner however, Ketamine produces better anaesthetic quality than propofol